2019
DOI: 10.1002/zaac.201900163
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Laser Induced Breakdown Spectroscopy (LIBS) to Study Catalyst Deactivation of V2O5/γ‐Al2O3 as Compared to Inductively Coupled Plasma Optical Emission Spectrometry

Abstract: Laser Induced Breakdown Spectroscopy (LIBS) method is introduced as a novel approach in this work to study catalyst deactivation of V 2 O 5 /γ--Al 2 O 3 for gas-phase dehydration of glycerol and producing acrolein. The LIBS results of V 2 O 5 /γ-Al 2 O 3 samples are compared with those data that are obtained by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). Experimental data of LIBS 1057 data specify that line intensities of vanadium are decreased by deactivation of V 2 O 5 /γ-Al 2 O 3 cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…A similar study was also reported for the monitoring of V leaching from V 2 O 5 /g-Al 2 O 3 catalysts during the gas phase dehydration of glycerol. 136 However, little was detailed regarding the preparation of the sample.…”
Section: Catalystsmentioning
confidence: 99%
“…A similar study was also reported for the monitoring of V leaching from V 2 O 5 /g-Al 2 O 3 catalysts during the gas phase dehydration of glycerol. 136 However, little was detailed regarding the preparation of the sample.…”
Section: Catalystsmentioning
confidence: 99%
“…Since the mid 1980s, intensive research efforts had been devoted to the solidification of organic laser dyes, which might bring benefits such as non‐toxic and maintenance‐free in comparison with liquid dye lasers . In recent years, significant progresses had been witnessed in this field, i.e., solid‐state tunable laser media were activated by dye molecules, which were demonstrated to be crucially important tools in a wide variety of novel applications, from spectroscopy to isotopic separation, photochemistry, medical diagnosis and therapy . By utilizing various host matrices, for instances, the fluorinated polymers,, organic‐inorganic hybrid materials,, , and nano‐particles dispersed polymers,, , as the solid hosts, and synthesizing various dye molecules, e.g., pyrromethene and perylene dyes in the yellow and red spectral ranges, the durability or longevity of the organic tunable lasers, which had been regarded as one of the most crucial obstacles for practical use from long before, was improved to an extent that problems related to commercial employment were partially resolved.…”
Section: Introductionmentioning
confidence: 99%